Revisiting the Benefits of Integrating Multicultural and Workforce Diversity Frameworks and Practices in Organizational Settings: Suggestions for Advancing Contemporary Leadership Practices - Scott, Chaunda L. (Journal of Organizational Psychology, 2025)
Recognized contemporary leadership practices such as Servant Leadership (Greenleaf, 2007), Transcendent Leadership (Crossan., Vera., & Nanjad, 2008) and Strategic Leadership (Beatty & Quinn, 2010),) are known for offering an understanding of the ways that leadership skills can be utilized in a variety of organizational settings. These well-known leadership practices are also known for underscoring the kinds of traits and behaviors that leaders should possess to lead and manage their employees and achieve organizational goals. However, one area that is absent from contemporary leadership practices is a focus on the kinds of multicultural and workforce diversity leadership knowledge, skills, and abilities that organizational leaders should possess to lead and manage a range of human diversities effectively in various organizational settings. The aim of this article is to: 1) share examples of existing multicultural and workforce diversity frameworks and practices that offer insights for advancing contemporary leadership practices: and 2) highlight the benefits of integrating multicultural and workforce diversity leadership frameworks and practices in present-day organizational settings.